2022
DOI: 10.1002/jhet.4548
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biological evaluation, and computational study of benzimidazole hybrid thiosemicarbazide derivatives

Abstract: The antimicrobial, anti‐tubercular, antimalarial, and antioxidant properties of a series of benzimidazole hybrid thiosemicarbazide derivatives (7a–o) were investigated in vitro. IR, 1H‐NMR, 13C‐NMR, and ESI‐MS spectra were used to describe and elucidate the synthesized compounds. The majority of the compounds studied have excellent antibacterial and antioxidant properties. In addition, an in silico investigation was conducted. By calculating ADME‐Tox descriptors, all freshly synthesized molecules were shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…assessed the anti‐malarial scaffolds as benzimidazole‐based thiosemicarbazide derivatives ( 3 ) against the P. falciparum strains (Figure 4). [45] The p ‐chloro phenyl derivative ( 3 ) was found with good anti‐malarial activity (IC 50 of 0.15 μg/mL) than quinine (IC 50 of 0.268 μg/mL). Furthermore, these compounds have been subjected to evaluation for their anti‐oxidant and anti‐(myco)bacterial activity along with the studies using the in silico tools.…”
Section: Heterocycles As Privileged Scaffold Towards Anti‐malarial Ag...mentioning
confidence: 99%
See 1 more Smart Citation
“…assessed the anti‐malarial scaffolds as benzimidazole‐based thiosemicarbazide derivatives ( 3 ) against the P. falciparum strains (Figure 4). [45] The p ‐chloro phenyl derivative ( 3 ) was found with good anti‐malarial activity (IC 50 of 0.15 μg/mL) than quinine (IC 50 of 0.268 μg/mL). Furthermore, these compounds have been subjected to evaluation for their anti‐oxidant and anti‐(myco)bacterial activity along with the studies using the in silico tools.…”
Section: Heterocycles As Privileged Scaffold Towards Anti‐malarial Ag...mentioning
confidence: 99%
“…al. synthesized a newer complex of copper (I) with chloroquine [Cu(CQ)(PPh 3 ) 2 ]NO 3 (45) and reported that complexation of copper with chloroquine in the betterment of anti-malarial activity against chloroquine-susceptible Pf3D7 (IC 50 of 6 nM) and chloroquine-resistant PfW2 (IC 50 of 231 nM) strains with SI of 2284 and 106.4, respectively. [76] Further, the spectrophotometric titrations helped to study the inhibition of DNA synthesis and β-hemozoin formation.…”
Section: Quinolinementioning
confidence: 99%